Population-based temporal trends and ethnic disparity in breast cancer mortality in South Africa (1999-2018): Joinpoint and age–period–cohort regression analyses - Olorunfemi, Gbenga; Libhaber, Elena; Ezechi, Oliver Chukwujekwu; Musenge, Eustasius (Frontiers in Oncology, 2023)
Abstract Globally, breast cancer is the leading cause of cancer deaths, accounting for 15.5% of female cancer deaths in 2020. Breast cancer is also the leading cause of female cancers in South Africa. The rapid epidemiological transition in South Africa may impact on the trends in breast cancer mortality in the country. We therefore evaluated the trends in the breast cancer mortality in SA over 20 years (1999-2020). Methods. Join point regression analyses of the trends in crude and age-standardised mortality rates (ASMR) of breast cancer among South African women were conducted from 1999 to 2018 using mortality data from the Statistics SA. Age-period-cohort regression analysis was then conducted to evaluate the independent effect of age, period and cohort on breast cancer mortality and analysis was stratified by ethnicity. Results: The mortality rate of breast cancer (from 9.82 to 13.27 per 100,000 women) increased at about 1.4% per annum (Average Annual Percent Change (AAPC): 1.4%, 95%CI:0.8 – 2.0, P-value < 0.001). Young women aged 30-49 years (1.1%-1.8%, P-value< 0.001) had increased breast cancer mortality. The risk of breast cancer mortality increased among successive birth cohorts from 1924-1928 but decreased among recent cohorts born from 1989-1993. In 2018, the breast cancer mortality rate among Blacks (9.49/100,000 women) was about half of the rates among the non-Blacks. (Coloureds: 18.11 per 100,000 women; Whites: 17.77/ 100,000 women; Indian/Asian: 13.24 per 100,000 women) Conclusions Contrary to the trends in high- and middle-income countries, breast cancer mortality increased in South Africa especially among young women. Breast cancer prevention programs should be intensified and should also target young women. The marked disparity in ethnic burden of breast cancer should be considered during planning and implementation of interventions.